Highly Diastereoselective Syntheses of Spiro‐Oxindole Dihydrofuran Derivatives in Aqueous Media and Their Antibacterial Activity. Issue 33 (29th November 2017) - Gupta, Naveen; Bhojani, Gopal; Tak, Rajkumar; Jakhar, Ajay; Khan, Noor‐ul H.; Chatterjee, Shruti; Kureshy, Rukhsana I.
Abstract: A series of substituted spiro‐oxindole dihydrofuran ring derivatives were synthesized in good yields up to 94% and excellent diastereoselectivity ≥99% by simple tandem Michael ‐ cyclization in aqueous media using DABCO (1, 4‐diazabicyclo[2.2.2]octane) as a catalyst and SDS (sodium dodecyl sulfate) as a promoter at ambient temperature. These molecules displayed promising antibacterial activity in vitro against pathogenic strains viz Vibrio cholerae, Escherichia coli, Bacillus subtilis, Bacillus licheniformis, Pseudomonas fluorescens, Salmonella enterica, Shigella flexneri and Shigella boydii with MIC (minimum inhibitory concentration), MBC (minimum bactericidal concentration) and IC50 (inhibitory concentration) values better than the standard antibiotic ampicillin. Abstract : A new series of substituted spiro‐oxindole derivatives were synthesized, which showed high antibacterial activity against eight pathogenic strains with high potency than ampicillin taken as standard. This protocol requires catalytic amount of DABCO as catalyst and water as reaction media. High yields were observed and selectivity >99% in all the cases.